Determinan Penentu Tingkat Pemahaman Akuntansi Dalam Pembelajaran Daring Di Era Covid-19 Mahasiswa Akuntansi Universitas Muhammadiyah Jember - Odi Aldiansyah; Ibna Kamelia Fiel Afroh; Retno Murwanti (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This study aims to examine the independent variables of emotional intelligence, intellectual intelligence, spiritual intelligence, interest in learning and the availability of IT on the dependent variable of accounting understanding in online learning. The population in this study were students who were still active in the accounting study program until the class of 2022. While the sample used was 87 respondents. The primary data used is the results of questionnaire answers distributed via Google forms and secondary data in this study is student data obtained from the Academic Bureau of the Faculty of Economics and Business, University of Muhammadiyah Jember. Before conducting the data analysis test in this study, the validity and reliability tests were carried out first and the classical assumption test was carried out. With the results of the study, the variables of emotional intelligence, intellectual intelligence, spiritual intelligence, interest in learning and the availability of IT in Partial and Simultaneous affect the understanding of accounting in learning from students of the accounting study program at the University of Muhammadiyah Jember.